MSMEs go digital: Motion graphic promotional video training for sales improvement - Sari, Intan Permata; Juhana, Agus; Prana, Irvan Satrya; Permana, Fahmi Candra (Community Empowerment, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in inclusive and sustainable economic development. Despite the significant potential of the digital economy to enhance market access for MSMEs, the optimal utilization of technology among these businesses remains limited. Motion graphics, as a popular animation technology in digital promotion, offer a solution that is relatively easy for MSMEs to learn and implement. This program is designed to enhance the application of appropriate technology in empowering MSMEs through the utilization of motion graphic-based promotional videos, with the ultimate goal of increasing sales. The implementation method of this PkM program employs a participatory approach encompassing needs identification, intensive training, and continuous mentoring stages. Evaluation results indicate a significant increase in the understanding and skills of MSME participants, with an average score increase of 4.82. Thus, motion graphic-based promotional video training proves effective in improving the digital capacity of MSME actors, potentially serving as a strategic solution to address the limited utilization of digital promotion technology and drive their economic growth.